The effects of European integration on the development of cross-border transport infrastructure: The example of Slovak–Polish boundary - MICHNIAK, Daniel (Discussion Papers, 2011)
European integration is one of the most important processes (phenomena) that have affected Europe, particularly fields like politics, law, economics, and also social and cultural fields during the last decades. An important milestone in the process of European integration was the gradual integration of several former socialist countries into the EU, and later the Schengen agreement. The aim of this paper is the analysis of effects of the European integration on the development of cross-border transport infrastructure with special attention to the Slovak–Polish boundary. In other words, some examples of development of cross-border infrastructure on the Slovak–Polish border that use the EU funds will be presented. It is found that the new cross-border transport infrastructure helps to improve trans-border accessibility and enables to use the existing tourist potential, while certain strictly protected areas such as National Parks and Nature Reserves represent important barriers for cross-border movement and development of cross-border transport infrastructure.